A.07 Head circumference in preterm neonates: size at birth and postnatal growth predict neurodevelopment at 18 months. (17th June 2016) - Selvanathan, T; Chau, V; Brant, R; Synnes, A; Grunau, R; Miller, S
Abstract : Background: We determined the association between head circumference (HC) at birth and through neonatal intensive care with neurodevelopmental outcome in preterm neonates, accounting for brain injury on MRI. Methods: 169 neonates born 24-32 weeks gestation were studied prospectively with serial MRI. HC was measured at birth and discharge from neonatal intensive care. Outcome was assessed at 18 months corrected age using Bayley Scales of Infant & Toddler Development III motor and cognitive scores. Using multivariate linear regressions we evaluated the association between HC and outcomes, accounting for severity of brain injury and postnatal infection. Results: 46 neonates had HC <10 th percentile at birth (SHC) which predicted poorer motor ( 4 points; p=0.001) and cognitive ( 4 points; p=0.005) outcomes, relative to those with normal HC at birth. In 9 of these neonates, SHC persisted to discharge; they had dramatically lower motor scores (15 points; p=0.004) and cognitive scores (12 points; p<0.001), even after adjusting for known risk factors Those born with SHC whose HC normalized by discharge did not show significantly poorer outcomes than those born with normal HC. Conclusions: The relationship between small HC at birth and adverse neurodevelopmental outcomes can be attenuated with normalization of head growth through the period of neonatal intensive care.